2014
DOI: 10.1590/0104-1169.3222.2461
|View full text |Cite
|
Sign up to set email alerts
|

The effects of compensatory workplace exercises to reduce work-related stress and musculoskeletal pain

Abstract: OBJECTIVES: to assess the effect of a compensatory workplace exercise program on workers with the purpose of reducing work-related stress and musculoskeletal pain. METHOD: quasi-experimental research with quantitative analysis of the data, involving 30 administrative workers from a Higher Education Public Institution. For data collection, questionnaires were used to characterize the workers, as well as the Workplace Stress Scale and the Corlett Diagram. The research took place in three stages: first: pre-test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 19 publications
1
22
0
12
Order By: Relevance
“…Thus, muscle conditioning is important for these professionals in order reduce the risk of muscle and spinal injuries, and it can be obtained through physical activity in the workplace (30)(31) . In this sense, a quasiexperimental study carried out with workers from a Brazilian higher education institution identified that physical activity at the workplace reduced musculoskeletal pain, but did not significantly reduce occupational stress levels (32) , a result similar to the present study. The positive effects of physical activity on mental health are well documented; however, the impact of physical activity promoted on the workplace is still controversial.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, muscle conditioning is important for these professionals in order reduce the risk of muscle and spinal injuries, and it can be obtained through physical activity in the workplace (30)(31) . In this sense, a quasiexperimental study carried out with workers from a Brazilian higher education institution identified that physical activity at the workplace reduced musculoskeletal pain, but did not significantly reduce occupational stress levels (32) , a result similar to the present study. The positive effects of physical activity on mental health are well documented; however, the impact of physical activity promoted on the workplace is still controversial.…”
Section: Discussionsupporting
confidence: 87%
“…Entre as consequências físicas associadas à insatisfação e ao estresse crescente é comum identificarmos somatizações álgicas com uma direta influência na qualidade de vida do residente. A literatura já demonstrou presença de fadiga muscular e aumento do risco de aparecimento de complicações osteomioarticulares relacionadas ao trabalho -fruto, muitas vezes, de esforços excessivos e posturas inadequadas associadas a abalos psicológicos [27][28][29][30] .…”
Section: Discussionunclassified
“…Estos, a su vez, podían comprender ejercicios posturales y de estabilización articular cervical y/o lumbar. El programa de ejercicios contenía actividades tanto de pie como sentado (5,25,26) .…”
Section: Folletos Informativos Más Pausas Activas Supervisadasunclassified